Kesejahteraan psikologi dan sumber stres kerja: kajian rintis dalam kalangan anggota Penguat kuasa Kementerian Perdagangan Dalam Negeri dan Hal Ehwal Pengguna - Leong, Jong Jee; Muhammad Idris Bullare @ Bahari,; Mohd. Dahlan Abdul Malek, (Penerbit Universiti Kebangsaan Malaysia, 2019)
This study aims to identify the level of psychological well-being and job stress among the enforcement officer of the Ministry of Domestic Trade and Consumer Affairs (KPDNHEP). A bunch of studies only focus on exploring the psychological well-being of policemen while there are still 19 other enforcement agencies in Malaysia that need to be addressed when studies on the psychological well-being of enforcement members are carried out. The impact of the stressors on the work of KPDNHEP enforcement personnel is also rarely given attention by local researchers. A total of 60 KPDNHEP enforcement members were involved in this study. The cluster sampling method was used and samples from the KPDNHEP state offices of Selangor, Sarawak and Sabah were randomly selected to participate in this study. Ryff's Psychology Well-Being Scale (PWBS) is used to measure the level of psychological well-being of the respondents while the Job Stress Survey (JSS) is used to determine the level of job stress of respondents. The data obtained were analyzed by using the IBM SPSS Statistic version 20. The results showed that KPDNHEP enforcement officers had a high degree of psychological well-being. However, they experience a relatively low overall job stress. The job pressure and lack of support has contributed to a moderate level of job stress. It is hoped that more psychological well-being and job stress studies will be conducted on other enforcement agencies in Malaysia in the future.